Influence of indigenous mixotrophic bacteria on pyrite surface chemistry: Implications for bioflotation - Edy Sanwani; Nuslia Bayangkara Lamandhi; Halimatul Husni; Siti Khodijah Chaerun; Widi Astuti; Fika Rofiek Mufakhir (Microbiology Indonesia, 2020)
Given the low-cost and eco-friendly method, biotechnology has been widely utilized in industries as an alternative for physical and chemical processes, including in the biomining process (e.g., bioflotation and biobeneficiation). However, the use of biochemical reagent, which is selective for certain minerals, has not been well studied. This research was aimed to investigate the potential use of biosurfactant-producing mixotrophic bacteria as an alternative to chemical reagents during bioflotation and biobeneficiation process. Thirteen bacterial strains were investigated for their ability to produce biosurfactants and their effects on the surface properties of pyrite minerals. Bacteria-pyrite interaction experimental results showed that pyrite surface properties became more hydrophilic in the experimental systems inoculated with bacteria adapted with pyrite for 48 h than that without bacterial adaptation to pyrite, which was evidenced by the decrease in the contact angle of pyrite minerals by up to 50%. This evidence was also confirmed by the highest emulsifying index value (51.6%) attained during the bacteria-pyrite interaction. Hence, these bacteria can potentially be applied to selective flotation as pyrite depressants.